2000
DOI: 10.1164/ajrccm.161.6.9906130
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Th1/Th2 Paradigm in Whole Blood in Atopy and Asthma

Abstract: Atopy is characterized by an immune system that is biased to T helper cell, type 2 (Th2) activation. This condition predisposes to asthma, a disease in which a Th2 activation was found in blood and lungs. However, most blood studies have considered purified cells, which might give an incomplete view of immune reactions. In this study, we assessed in whole blood cultures the Th1/Th2 paradigm in atopy and asthma. Sixty-nine subjects (31 atopic asthmatics, six nonatopic asthmatics, 13 atopic nonasthmatics, and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
134
5
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(159 citation statements)
references
References 30 publications
19
134
5
1
Order By: Relevance
“…In a mouse model of virally induced AHR and airway remodelling, there was no attenuation of these parameters in IFN-c-deficient mice [60]. Interestingly, there is evidence that IFN-c expression in peripheral blood CD8+ T-cells correlated with AHR in asthmatic subjects [61], and a recent study found that IFN-c production in cord blood CD8 T-cells predicted subsequent allergic sensitisation [62]. IFN-c-expressing lymphocytes are present in the lungs or sputum of some subjects with asthma [63,64], and it would seem likely that IFN-c-secreting cytolytic CD8+ cells would be recruited to the lung during virally triggered exacerbations.…”
Section: Th2 Cells Asthma and Atopymentioning
confidence: 99%
“…In a mouse model of virally induced AHR and airway remodelling, there was no attenuation of these parameters in IFN-c-deficient mice [60]. Interestingly, there is evidence that IFN-c expression in peripheral blood CD8+ T-cells correlated with AHR in asthmatic subjects [61], and a recent study found that IFN-c production in cord blood CD8 T-cells predicted subsequent allergic sensitisation [62]. IFN-c-expressing lymphocytes are present in the lungs or sputum of some subjects with asthma [63,64], and it would seem likely that IFN-c-secreting cytolytic CD8+ cells would be recruited to the lung during virally triggered exacerbations.…”
Section: Th2 Cells Asthma and Atopymentioning
confidence: 99%
“…The Simultaneous Multianalyte Reagent Technology method is a flow cytometric immunoassay performed on fluorescent and Ab-coated microspheres (30), allowing the simultaneous titration of IL-1␤, IL-4, IL-6, IL-10, and IL-12p40, with a sensitivity of 0.5-1.5 pg/ml. It has been described extensively previously (31).…”
Section: Cytokine Production and Titrationmentioning
confidence: 99%
“…In nonatopic asthma, a neutrophil inflammatory process may occur. 18 Tregs (regulatory T cells) reduce proliferation and decrease Th2 levels and hence the inflammatory process in asthma cases. 19 Tregs are essential for induction and maintenance of tolerance against antigens.…”
mentioning
confidence: 99%